Luminescence of gallium-containing complex oxide crystal - Shevchuk, V.N. (Functional Materials, 2005)
Luminescence spectra of garnet Nd₃Ga₅О₁₂ and of acentric Ca-gallogermanate Сa₃Ga₂Ge₄О₁₄:Nd³⁺ crystals under pulsed X-ray excitation (-1.5 ns) in 200-500 nm range are considered. The luminescence measurements carried out at 80 К and 295 К. Time characteristics of fast (-1 ns) emission components of the crystals are evaluated. The narrow luminescence bands (slow components) are ascribed to transitions from the ²F2₅/₂ level of Nd³⁺ ion.